2022
DOI: 10.1007/s00394-022-03024-5
|View full text |Cite
|
Sign up to set email alerts
|

Milk fat globule membrane plus milk fat increase docosahexaenoic acid availability in infant formulas

Abstract: Purpose Milk fat globule membrane (MFGM) has components with emulsifier properties that could affect the provision of substrates to the brain. We evaluated the effects of MFGM plus milk fat addition to infant formulas on docosahexaenoic acid (DHA) availability and gut development. Methods In Experiment 1, suckling piglets were divided into 3 groups: Group L1 (n = 8): fed with a vegetal fat formula with palm oil; L2 (n = 8): canola oil formula and L3 (n = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…It influences the development of myelin phospholipids in the central and peripheral nervous systems. 35 Our study found that the addition of OPO and MFGM in formula milk powder has a certain promotional effect on the development of gross motor skills, fine motor skills, adaptive behavior, and language abilities in four-month-old infants (closer to the state of breastfeeding), consistent with the findings of Gázquez et al 36 However, unlike previous studies, our research suggests that the impact of OPO and MFGM on infant neurodevelopment occurs earlier, possibly because our study subjects were full-term infants, not preterm infants. Studies by Litamanovitz et al 37 and Kennedy et al 38 demonstrated that formula milk powder enriched with OPO can promote increased bone mineral density in infants, which aligns with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…It influences the development of myelin phospholipids in the central and peripheral nervous systems. 35 Our study found that the addition of OPO and MFGM in formula milk powder has a certain promotional effect on the development of gross motor skills, fine motor skills, adaptive behavior, and language abilities in four-month-old infants (closer to the state of breastfeeding), consistent with the findings of Gázquez et al 36 However, unlike previous studies, our research suggests that the impact of OPO and MFGM on infant neurodevelopment occurs earlier, possibly because our study subjects were full-term infants, not preterm infants. Studies by Litamanovitz et al 37 and Kennedy et al 38 demonstrated that formula milk powder enriched with OPO can promote increased bone mineral density in infants, which aligns with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…The structures of PLs and gangliosides found in bMFGM could potentially enhance the uptake of DHA from milk triacylglycerol and increase its uptake in tissues. The developing brain has the ability to synthesize and incorporate DHA from blood vessels into membrane PLs, which can result in improved neurite outgrowth, synaptogenesis, and neurogenesis ( 35 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, infants consuming an IF containing a mixture of dairy lipids and vegetable oil were shown to have higher erythrocyte n-3 LCPUFAs compared to infants who were fed an IF containing vegetable oil only ( 45 ). Using animal models, several studies confirmed higher n-3 PUFAs in brain tissue as a result of dairy lipid exposure ( 38 , 46 , 47 ), but others did not ( 48 ), and the effects on functional outcomes such as neuroplasticity and cognition appear to be mixed ( 47 , 49 , 50 ). Currently, the evidence is insufficient to confirm a role of sn-2 PA supplementation on infant neurodevelopmental outcomes ( 51 ).…”
Section: Discussionmentioning
confidence: 99%